Diagnostic decision-making tool for imaging term neonatal bowel obstruction. Issue 3 (March 2021) - Tsitsiou, Y.; Calle-Toro, J.S.; Zouvani, A.; Andronikou, S.
Abstract : Term neonatal bowel obstruction is common, and absence of treatment is potentially catastrophic. There is a relatively narrow differential diagnosis, with causes categorised as either low or high bowel obstruction. The commonest causes of low bowel obstruction include anorectal malformations (ARM), Hirschsprung's disease, ileal atresia, meconium ileus, meconium plug, and colonic atresia. The commonest causes of high bowel obstruction include duodenal atresia, duodenal stenosis/web, jejunal atresia, and malrotation with volvulus (and hypertrophic pyloric stenosis usually presenting in slightly older infants). Diagnosis can be decided using a step-wise binary decision tool that includes the appropriate imaging steps and evaluation of bowel calibre. This paper presents the decision-making tool from the presenting features, through plain radiographic findings and, where necessary, the additional radiological investigations to assist the general radiologist, novice paediatric radiologist and paediatric surgeon. The tool is pictorial, with the radiological findings accompanied by eight schematics, serving as a simplified visual aid for memorizing the imaging patterns of the differential diagnosis. The imaging and decision-making steps allow for a rapid, simplified diagnosis that can benefit patients by recommending when to perform surgery, when to perform further imaging, and when imaging can act in a therapeutic manner.